Review of Hydropower Plant Models - FIFATIN, François-Xavier; ACAKPOVI, Amevi; HAGAN, Essel Ben (My University, 2014)
This paper consists of an extensive review on the modeling of hydropower plant. First a background was provided on all components needed to develop a full and comprehensive model on hydropower plant including penstock, governor, turbine and generator. The review of existing models was started with simple analytical models that were followed by system modelling. The complexity of modeling the dynamic aspect of water flowing through the penstock as well as the opening and closing of wicket gate have led to the development of complex control systems to model hydropower plant. Those complex models were rather represented as systems instead of been analytical. They are mostly equipped with numerous feedback as well as modern control systems such as fuzzy logic and PID control logic that improves their performances. However, these models are most often constructed and simulated with software of which Matlab is a fundamental one. In line with this, the paper investigated a simulation of hydropower plant including a model of hydraulic turbine, governor and synchronous machine, all simulated under Matlab software. A three phase to ground fault was introduced in the model at t=0.2s and remove after t=0.4s and this shows that the generated voltage quickly regained its stability due to the high excitation voltage that was maintained by the PID control system incorporated in the hydraulic turbine model. The speed of the motor also regained stability but this case was slower than the voltage one. In all, simulation results showed a perfect generation of energy from hydropower plant that was robust enough to resist faults.
Keywords: Hydraulic turbine; penstock; governor; synchronous; generator; system simulation.